Kinetic Study of Aluminum – Alginate Catalyzed Esterification of Lactic Acid with 1-Butanol - Kanungnit Chawong; Chitkamon Poncharee; Boonpradab Daengpradab; Panarat Rattanaphanee (ASEAN Journal of Chemical Engineering, 2019)
Aluminum-alginate catalyst prepared from aluminum chloride and inexpensive biopolymer sodium alginate is used in lactic acid esterification with 1-butanol. Effect of initial reactant molar ratio, catalyst loading and reaction temperature on the acid conversion is investigated. Maximum conversion of about 81.2% was achieved after 6 h of reaction at 85°C with initial 1-butanol-to-lactic-acid molar ratio of 5 and catalyst loading of 1%w/v. Experimental kinetic data are correlated by pseudo-homogeneous model using UNIFAC to describe non-ideality of the reaction components. Satisfactory agreement between the experimental and calculated data is achieved. The specific rate and equilibrium constant for this reaction are reported.